Location matters: left heart obstruction in pregnancy. (January 2016) - Fuchs, Margaret; Zaidi, Ali N.; Rose, Justin; Sisk, Tracey; Daniels, Curt J.; Bradley, Elisa A.
Abstract: Objectives: Left heart obstruction in pregnancy is associated with higher rates of morbidity/mortality. The primary aim of this study was to evaluate maternal cardiovascular, obstetric, and fetal/infant events in pregnant women with left heart obstruction. Study design: Pregnant women with current or repaired left heart obstruction were retrospectively analyzed (2000–2014): mitral stenosis, left ventricular outflow tract obstruction (subvalvar, valvar, supravalvar), and coarctation of the aorta. Maternal cardiovascular events were defined as: heart failure, arrhythmia, urgent/emergent cardiac surgery or percutaneous transcathter intervention, transient ischemic attack/cerebrovascular accident, and death up to 6 months postpartum. Results: There were 90 pregnancies in 67 women (29 ± 7 years old) who had 15 maternal cardiovascular events. Isolated mitral stenosis ( n = 6) or >1 serial left heart obstructive lesion ( n = 6) were the source of the event in the majority pregnancies. Women with isolated mitral stenosis had increased cardiovascular events compared to other single left heart obstructive lesions (OR 18.6, 95% CI: 3.8–91.1). If >1 serial obstructive lesion was present, there was also an increased risk of maternal cardiovascular events (OR 6.8, 95% CI: 1.6–29.1), however isolated mitral stenosis carried similar risk to serial left heart obstructive lesions (OR 2.7, 95% CI: 0.7–11.2). Baseline characteristics associated with events included: New York Heart Association functional class >2 (27% vs. 0, p < 0.001), any current left heart obstruction (73% vs. 36%, p = 0.01), severe left heart obstruction (40% vs. 29%, p < 0.001), and higher Cardiac Disease in Pregnancy ("CARPREG") score (1.2 ± 0.7 vs. 0.5 ± 0.7, p = 0.01). There was no difference in rate of obstetric/fetal/infant complications in women with cardiovascular events; however, term birth weight was lower (2.7 ± 0.5 vs. 3.1 ± 0.6 kg, p = 0.01). There was no maternal mortality. Conclusions: Isolated mitral stenosis and serial (>1) left heart obstructive lesions carry the highest risk of maternal cardiovascular events. We are the first to show higher event rates in women with serial left heart obstructive lesions. The data supports the need for specialized and experienced high-risk obstetric-cardiac teams to care for women with left heart obstruction, and demonstrates excellent outcomes in a complex cohort of pregnant women with all types of left heart obstruction.